FoxO1-GAB1 axis regulates homing capacity and tonic AKT activity in chronic lymphocytic leukemia - Seda, Vaclav; Vojackova, Eva; Ondrisova, Laura; Kostalova, Lenka; Sharma, Sonali; Loja, Tomas; Mladonicka Pavlasova, Gabriela; Zicha, Daniel; Kudlickova Peskova, Marie; Krivanek, Jan; Liskova, Kvetoslava; Kren, Leos; et al. (Blood, 2021)
Recirculation of chronic lymphocytic leukemia (CLL) cells between the peripheral blood and lymphoid niches plays a critical role in disease pathophysiology, and inhibiting this process is one of the major mechanisms of action for B-cell receptor (BCR) inhibitors such as ibrutinib and idelalisib. Migration is a complex process guided by chemokine receptors and integrins. However, it remains largely unknown how CLL cells integrate multiple migratory signals while balancing survival in the peripheral blood and the decision to return to immune niches. Our study provided evidence that CXCR4/CD5 intraclonal subpopulations can be used to study the regulation of migration of CLL cells. We performed RNA profiling of CXCR4dimCD5bright vs CXCR4brightCD5dim CLL cells and identified differential expression of dozens of molecules with a putative function in cell migration. GRB2-associated binding protein 1 (GAB1) positively regulated CLL cell homing capacity of CXCR4brightCD5dim cells. Gradual GAB1 accumulation in CLL cells outside immune niches was mediated by FoxO1-induced transcriptional GAB1 activation. Upregulation of GAB1 also played an important role in maintaining basal phosphatidylinositol 3-kinase (PI3K) activity and the "tonic" AKT phosphorylation required to sustain the survival of resting CLL B cells. This finding is important during ibrutinib therapy, because CLL cells induce the FoxO1-GAB1-pAKT axis, which represents an adaptation mechanism to the inability to home to immune niches. We have demonstrated that GAB1 can be targeted therapeutically by novel GAB1 inhibitors, alone or in combination with BTK inhibition. GAB1 inhibitors induce CLL cell apoptosis, impair cell migration, inhibit tonic or BCR-induced AKT phosphorylation, and block compensatory AKT activity during ibrutinib therapy.
Keywords: Proto-Oncogene Proteins c-akt; Cell Line, Tumor; Adenine; Adaptor Proteins, Signal Transducing; Up-Regulation; Leukemia, Lymphocytic, Chronic, B-Cell; adaptorové proteiny signální transdukční; lidé; upregulace; signální transdukce; Forkhead Box Protein O1; Signal Transduction; regulace genové exprese u leukemie; pohyb buněk; protoonkogenní proteiny c-akt; adenin; Piperidines; Gene Expression Regulation, Leukemic; Cell Movement; forkhead box protein O1; piperidiny; chronická lymfatická leukemie; nádorové buněčné linie; Humans